2023
DOI: 10.1038/s42255-023-00803-0
|View full text |Cite
|
Sign up to set email alerts
|

SIRT2 regulates extracellular vesicle-mediated liver–bone communication

Abstract: The interplay between liver and bone metabolism remains largely uncharacterized. Here, we uncover a mechanism of liver-bone crosstalk regulated by hepatocyte SIRT2. We demonstrate that hepatocyte SIRT2 expression is increased in aged mice and elderly humans. Liver-specific SIRT2 deficiency inhibits osteoclastogenesis and alleviates bone loss in mouse models of osteoporosis. We identify leucine-rich α-2-glycoprotein 1 (LRG1) as a functional cargo in hepatocyte-derived small extracellular vesicles (sEVs). In SIR… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(9 citation statements)
references
References 63 publications
0
9
0
Order By: Relevance
“…61,62 Recent research has revealed that hepatocyte SIRT2 also plays a crucial role in the liver-bone axis, maintaining bone homeostasis and preventing osteoporosis. 63 This study showed that hepatocyte SIRT2 expression is increased in aged mice and older patients. Liver-specific SIRT2 deficiency (SIRT2-KO hep ) obviously inhibits osteoclastogenesis and alleviates osteoporosis in aged and postmenopausal osteoporosis mouse models.…”
Section: Sirt2mentioning
confidence: 79%
See 1 more Smart Citation
“…61,62 Recent research has revealed that hepatocyte SIRT2 also plays a crucial role in the liver-bone axis, maintaining bone homeostasis and preventing osteoporosis. 63 This study showed that hepatocyte SIRT2 expression is increased in aged mice and older patients. Liver-specific SIRT2 deficiency (SIRT2-KO hep ) obviously inhibits osteoclastogenesis and alleviates osteoporosis in aged and postmenopausal osteoporosis mouse models.…”
Section: Sirt2mentioning
confidence: 79%
“…The regulation of sEVs-LRG1-BMDM-p65 axis by hepatic SIRT2 might lead to effective therapeutic targets for treating osteoporosis. 63…”
Section: Sirt2mentioning
confidence: 99%
“…In addition, SIRT2 can promote OB proliferation and enhance activity through SIRT2/RUNX2 cascade regulation ( 63 ). Other studies have shown that hepatic SIRT2 gene defects can inhibit OC production and attenuate bone loss through liver-bone communication ( 64 ). FGF23 can inhibit the conversion of 25-hydroxy vitamin D to active 1,25(OH)2D3 by targeting the renal proximal tubule ( 65 ) and also affects bone mineralization and bone homeostasis by inhibiting OB function, which ultimately leads to bone destruction and increased fracture risk ( 66 ).…”
Section: Discussionmentioning
confidence: 99%
“…Acting as a nutrient and energy metabolic center, the communication between liver and other solid organs has been deeply recognized. However, much less study was conducted about the relationship between liver and bone, especially OCY, even though OCY-mediated skeletal health is tightly correlated with liver disease ( 83 ). Clinical data identified that almost all patients who suffered from chronic liver diseases associate with altered bone metabolism, particularly severe osteoporosis, leading to a novel research area named hepatic osteodystrophy ( 84 ).…”
Section: Liver–ocy Communicationmentioning
confidence: 99%